Hubungan Aktivitas Fisik dengan Tekanan Darah pada Pasien Hipertensi Esensial di Puskesmas Ciledug - Eka Aisyatir Rodiyah; Hamed Oemar; Sidhi Laksono (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Hypertension is one of non communicable disease which has a high prevalence in Indonesia. Based on Basic Health Research in 2018 the are N 658.201 Indonesian citizens with hypertension. Hypertension have some of the risk factor include gender, age, and sedentary lifestyle. Physical activity can be a risk factor of hypertension if people do it rarely. This study use a quantitative approach. The research method is using a retrospective cross-sectional study. The study will be using the GPAQ questionnaire and blood pressure measurement. This study determine the relationship between physical activity and blood pressure in patients with essential hypertension. Data analysis of this research is using Spearman test. The result of data analysis showed that there was a significant relationship between physical activity and blood pressure in hypertensive patients at the Ciledug Health Centre p = 0,00, the result of this study have a fairly strong correlation with a negative correlation (r= -0,59). The conclusion of this study is there is a significant relationship between physical activity and blood pressure in patients with essential hypertension at the Ciledug Health Center.